Pathogenicity, Host Responses and Implications for Management of Enterohemorrhagic Escherichia coli O157:H7 Infection - Nathan K Ho; Aleah C Henry; Kathene Johnson-Henry; Philip M Sherman (Canadian Journal of Gastroenterology)
Enterohemorrhagic Escherichia coli serotype O157:H7 is a food- and waterborne pathogen that causes significant morbidity and mortality in both developing and industrialized nations. The present review focuses on the history, epidemiology and evolution of the pathogen; provides a mechanistic overview of major virulence factors (including Shiga toxins, locus of enterocyte effacement pathogenicity island and pO157 plasmid); discusses host immune responses to infection; considers available animal models; and provides an overview of current and potential future management considerations.